2018
DOI: 10.3390/su10061886
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Literacy on Ecotourism: A Study on Student Knowledge, Attitude, and Behavioral Intentions in China and Taiwan

Abstract: This study aims to gain further insights to Chinese and Taiwanese university students' environmental literacy on ecotourism. A structural equation model is developed and validated in an effort to explore the differences between Chinese and Taiwanese university students in terms of their environmental knowledge, environmental attitude, and behavioral intentions. The results showed that the ecotourism perception of Chinese and Taiwanese university students affect their behavioral intentions. Chinese university s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 54 publications
4
37
0
1
Order By: Relevance
“…1). This pattern is generally in line with the findings by Fang et al (2018), which indicated higher means among Taiwanese female university students for knowledge, attitudes and behavior intention within the environmental dimension. This has also been confirmed for Taiwanese undergraduate students (Liang et al 2018).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…1). This pattern is generally in line with the findings by Fang et al (2018), which indicated higher means among Taiwanese female university students for knowledge, attitudes and behavior intention within the environmental dimension. This has also been confirmed for Taiwanese undergraduate students (Liang et al 2018).…”
Section: Discussionsupporting
confidence: 90%
“…The mean difference between the Taiwanese and Swedish samples for sustainability behaviors is close to 0.7, a substantial difference on a scale ranging between 1 and 5, for which most responses are found within a smaller part of the scale (the upper half). The stronger knowingness and attitudes and weaker behaviors for the Swedish students compared to Taiwanese students give further support for the criticism of simplistic interpretations concerning causal relationships between knowledge, attitudes and behaviors (e.g., Kollmuss and Agyeman 2002;Booth 2009;Michalos et al 2012;Fang et al 2018;Liang et al 2018).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations